2020
DOI: 10.20964/2020.05.09
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of DNA-Based Biosensor for Electrochemically Identification of Transgenic Soybean

Abstract: Since the successful transformation of the first transgenic soybean, the variety and planting area of transgenic soybean have increased. Therefore, transgenic soybean identification has become a necessary procedure in gm research. The development of rapid, sensitive, high-throughput and newly automated detection methods has become a hot spot in the detection of transgenic products. In this paper, we modified a layer of a partially reduced graphene oxide film on the surface of an ionic liquid carbon paste elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
2
0
1
Order By: Relevance
“…Jamaluddin et al [60] used anthraquinone-2-sulphonic acid as a marker. Deng et al [61] used a label-free sensing technology to directly reflect the differences in DNA hybridization with changes in electrode performance. Ge et al [62] recently reported a CRISPR/Cas12a-mediated dual-mode PCR, genosensor, and sequence became burst keywords over the next few years, but they did not last very long.…”
Section: Keyword Analysis and Evolution Of The Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Jamaluddin et al [60] used anthraquinone-2-sulphonic acid as a marker. Deng et al [61] used a label-free sensing technology to directly reflect the differences in DNA hybridization with changes in electrode performance. Ge et al [62] recently reported a CRISPR/Cas12a-mediated dual-mode PCR, genosensor, and sequence became burst keywords over the next few years, but they did not last very long.…”
Section: Keyword Analysis and Evolution Of The Fieldmentioning
confidence: 99%
“…GM algae were used to enhance the sensing capabilities of the platform, which could be used to identify different herbicide subclasses. The authors of the second paper proposed a labeled electrochemical sensor to detect GM soybean [61]. This paper is also classified in Cluster #0.…”
Section: Keyword Analysis and Evolution Of The Fieldmentioning
confidence: 99%
“…Como os biossensores geralmente envolvem detecções de analitos em concentrações baixas ou o evento de bioreconhecimento produz um sinal baixo, os transdutores eletroquímicos são muito utilizados por serem sensíveis a pequenas mudanças na eletroatividade do eletrodo (DENG et al, 2020). Outras vantagens de biossensores eletroquímicos incluem: rápidos tempos de resposta; facilidade na aplicação e leitura dos dados; baixo custo e possibilidade de miniaturização (BLAIR e CORRIGAN, 2020).…”
Section: Biossensores Eletroquímicosunclassified